PRACTICAL APPLICATION OF INFORMATION TECHNOLOGIES IN SOCIAL WORK STUDIES - Virbalienė, Rita; Mačiuikienė, Diana; Jegelevičienė, Violeta; Januškevičiūtė, Asta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Applying flexible and innovative teaching methods allows to improve the content of learning and education, as well as its quality and relevance. Efforts are made to provide as many opportunities for distance learning and virtual mobility as possible by using the benefits provided by new technologies, improving the training process and adapting it to each individual. A case study strategy was chosen, as the study consists of one separate object which is one higher school that implements the Social Work study program. The conducted research is of the "one-time cross-section" type, as it is dedicated for a specific purpose, namely, the modernization of the social work study program. In 2022 - 2023, semi-structured interviews were made with students of the Social Work Program participating in an international project on the application of innovative technologies in social work. The purpose of the research is to reveal aspects of the practical application of information technologies in the process of social work studies.Based on the findings obtained during the interviews and the research presented in the theoretical part about the application of information technologies in the study process, information technologies were divided into three groups of tools: technical tools, digital content creation tools, communication, and collaboration tools. The research found that the following technical tools are used the most and most often during lectures: computer, smartphone, camera, sound speakers, microphone with integrated speaker, Bluetooth headphones, projector, printer, high-speed Internet connection and wireless (wifi) network. It was found that students use text editors, calculators, the tools for video creation, presentation creation, quiz creation and survey assessment programs during lectures. Most often, 3-5 times a week, students use the following means of communication and collaboration: social networks, audio, and video storage, learning environments, laboratories, conferences, chat programs.